The Influence of Macroeconomic Factors on the Volatility of Composite Price Stock Index: A Study on the Indonesia Stock Exchange - Mohammad Nugraha, Nugi; Herlambang, Deva; Novan Setiawan Nugraha, Deden; Amalia, Shendy (International Journal of Psychosocial Rehabilitation, 2020)
Composite stock price index volatility has experienced ups and downs in the last period due to internal and external factors of several companies. It has an impact on the national economic level and decreased investment climate. This research aims to determine the effect of macroeconomic factors on the volatility of the composite stock price index in the Indonesia stock exchange period 2013-2017. The research method used is purposive sampling with a total data of 300 samples. Multiple regression analysis at the 5% significance level through the application of the view program plus several forms of testing to produce an appropriate recommendation. The results showed that the factors of economic growth, the exchange rate and the price of gold significantly influenced the volatility of the composite stock price index, while the inflation factor did not significantly influence the volatility of the composite stock price index.